2004
DOI: 10.1111/j.0105-1873.2004.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity to patch tests with nickel sulfate and fragrance mix in infants

Abstract: The pattern of patch test reactivity to nickel sulfate and fragrance mix was studied with respect to patch test performance, reproducibility and clinical relevance in a population of unselected infants followed prospectively from birth to 18 months of age. TRUE Testtrade mark patches with nickel sulfate in 3 concentrations, 200, 66 and 22 microg/cm(2), and fragrance mix 430 microg/cm(2) were used. A likely case of nickel sensitivity was defined as a reproducible positive reaction with at least homogeneous eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 40 publications
1
29
0
3
Order By: Relevance
“…Hjorth (Hjorth, 1981) thought that patch test reactions in infants were predominantly irritant reactions, especially when testing with nickel sulfate. In a study of Jøhnke et al (Jøhnke et al, 2004) it was confirmed that increasing numbers of infants positively patch tested to nickel sulfate but most reactions were transient and probably irritant or non-specific nature. Experimental CA to plants of the Rhus genus has also been induced in infants, showing that sensitization is possible (Epstein, 1961).…”
Section: Prevalence Related To Agementioning
confidence: 91%
See 2 more Smart Citations
“…Hjorth (Hjorth, 1981) thought that patch test reactions in infants were predominantly irritant reactions, especially when testing with nickel sulfate. In a study of Jøhnke et al (Jøhnke et al, 2004) it was confirmed that increasing numbers of infants positively patch tested to nickel sulfate but most reactions were transient and probably irritant or non-specific nature. Experimental CA to plants of the Rhus genus has also been induced in infants, showing that sensitization is possible (Epstein, 1961).…”
Section: Prevalence Related To Agementioning
confidence: 91%
“…Of these, about 56-93% was of current relevance (Weston & Weston, 1984;Pevny et al, 1984b;Fisher, 1994a;Rudzki & Rebandel, 1996;Stables et al, 1996;Manzini et al, 1998;Bruckner et al, 2000;Machovcová et al, 2001;Wöhrl et al, 2003;Heine et al, 2004;Lewis et al, 2004;Jøhnke et al, 2004;Vozmediano & Hita, 2005;Wahlberg & Lindberg, 2006;Goossens & Morren, 2006;Jacob et al, 2008). Among the children with a positive patch test 3.2% to 54.4% had multiple contact allergies (Mortz & Andersen, 1999).…”
Section: Prevalence Of Contact Allergy In a Selected Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nickel is the most widespread allergen in the general population (Heim & McKean, 2009;Johnke et al, 2004) and is most often identified as the leading allergen in children (Tables 1 & 2). It accounts for up to 14.9% of positive patch tests (Dotterud and Falk, 1995) in asymptomatic children and is generally more frequent in females (Beattie et al, 2007;Brasch & Geier, 1997;Giordano-Labadie et al, 1999).…”
Section: Nickelmentioning
confidence: 99%
“…Importantly, young infants may also be sensitized to nickel. In a study of 543 infants followed from birth to age 18 months, 8.6% showed a reproducible positive reaction to this metal (Johnke et al, 2004). Ear piercing is often considered the major risk factor for becoming sensitized to nickel (Smith-Sivertsen et al, 1999).…”
Section: Nickelmentioning
confidence: 99%